Factors Associated With Marital Satisfaction in Infertile Couple: A Comprehensive Literature Review - Samadaee-Gelehkolaee, Keshvar (Glob J Health Sci, 2016)
BACKGROUND: Many factors impact on marital satisfaction. Related factors include demographic factors, assisted reproductive techniques, psychological health, quality of life, psychological, socioeconomic and family support, and sexual function. METHODS: This study is a literature review of research studies conducted on factors associated with marital satisfaction in infertile couples. The current literature review search was undertaken using multiple databases selected from articles pertinent to the study. The selection of subjects was undertaken from1990 through 2015. The methodological quality was analyzed based on a checklist adopted from a systematic review. Quality assessment of full text studies was finally carried out by two reviewers. RESULTS: The initial search yielded a list of 445 papers, and then reviewers studied titles and abstracts. Thereafter, 69 papers were incorporated, and researchers reviewed summaries of all of the searched articles. Finally, the researchers utilized the data gained from 64 full articles so as to compile this review paper. Reviewing the studies conducted on marital satisfaction, they classified related findings into 6 categories: demographic factors, using fertility assisting methods, psychological health, life quality, economic, social, and family support, and sexual function. CONCLUSION: The results of this review article depicted that various factors play role in creating marriage life satisfaction in an infertile couple, so that paying attention to them can play an important role in continuing their treatment. Thus, to identify such factors is considered essential in their treatment protocol highly based on culture. Of the drawbacks of this research is that it has tried at best to employ the studies belonging to diverse countries with different cultures. Also, the number of the papers was considerably limited.